Housing vulnerability, agricultural production, and goods lost estimated to floods in Rio Nuevo a rural community in Colombia - Urrea-Ceferino, Gloria; Pinto Suarez, Camila Andrea; Jimeno Carrascal, Dina Luz; Yanez Ventura, Daniela Alejandra; Tapia Contreras, Hernán José (Economia agro-alimentare/Food Economy - Open Access, 2023)
Floods affect households, crops, and assets, especially in rural areas in Colombia; due to the lack of risk management plans, settlements without core services and land use planning, atypical natural phenomena, and climate change. The floods recorded since 1964, in the rural community of Rio Nuevo in the department of Córdoba, but there is a lack of estimates of the economic losses and housing vulnerability. The research aim was to determine the degree of physical vulnerability and estimated economic losses in crops and goods due to flooding in the local community of Río Nuevo, Valencia Town. The methodological guide for the elaboration of departmental plans for risk management (known in Spanish as PDGR), and the methodology for the economic valuation of potential direct tangible damages, was selected the variables (age, construction, regulations, soil, walls, floors, goods, and crops), questions, surveys to population, available data, proceed to process the information, elaborate maps and analyze. The results reveal physical vulnerability high in Rio Nuevo, with a value of 0.63 on a scale of 0 to 1. The rural community houses built located at a distance of fewer than 30 meters, mainly with wood, the soil of alluvial deposits, faced floods, humidity damages, hardening resistance, and non-quality life. The economic losses estimated between goods and crops were US174200.22. A poverty condition, poor infrastructure, and unfavorable places, hamper improve the quality of the people. Colombian government need to excecute a proper infrastructure investment to reduce persistence vulnerability and relocated this riverside area, according to its culture and traditions, and protect the economy around crops